Graph Database Modelling on Malay Architecture IFC Data - Muhammad Ariful Furqon; Gun Faisal; Nina Fadilah Najwa (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Architecture is the manifestation of society and its cultural practice. Preserving the architecture is an important thing that must be done both physically and digitally. One of the architectural cultures that must be preserved is Malay architecture. A method to preserve Malay architecture is to model it in the form of a graph database. Graph databases have shown excellent capabilities in understanding and accessing complex and rich datasets in many different domains. In this study, a graph database was modelled on the Malay architecture's Industry Foundation Classes (IFC) data. The methodologies used in this study were: (1) generate Malay architecture's IFC from Building information modelling (BIM) software; (2) Parse IFC; (3) IFC meta-data graph modelling; and (4) IFC object graph modelling. The expected result of this research is a graph database modelling which will be developed further by defining queries to solve problems of Malay architectural models.